Comparison of invasive micropapillary and triple negative invasive ductal carcinoma of the breast. Issue 6 (December 2015) - Chen, Hong-liang; Ding, Ang
Abstract: Background: Invasive micropapillary carcinoma (IMPC) of the breast and triple negative breast cancer (TNBC) are both aggressive subtypes, but little information is available on their comparison. Patients and methods: Retrospective analysis of 95 IMPC and 200 TNBC-IDC (invasive ductal carcinoma) was conducted to compare the clinicopathologic characteristics and survivals. Results: For IMPC, pN was the independent prognostic factor of local-regional recurrence free survival (LRRFS) ( P = 0.045) and metastasis free survival (MFS) ( P = 0.048), but not of overall survival (OS) ( P = 0.165). For TNBC, pT and lymphovascular invasion (LVI) were both independent prognostic factors of MFS (pT: P = 0.006, LVI: P = 0.010) and OS (pT: P = 0.006, LVI: P = 0.001), but not for LRRFS (pT: P = 0.060, LVI: P = 0.503). IMPC exhibited more aggressive features than TNBC, including larger tumor size, a greater proportion of nodal involvement, and an increased incidence of LVI. After a median follow-up duration of 61 months, 5y-LRRFS rate was lower in IMPC than in TNBC, in entire cohort (71.4 ± 4.8% vs. 89.8 ± 2.2%, P < 0.001) and in node positive cases (64.2 ± 5.9% vs. 81.7 ± 4.4%, P = 0.048). A tendency of lower 5y-MFS rate was observed in TNBC compared with in IMPC, in node positive cases (63.8 ± 5.5% vs. 74.8 ± 5.5%, P = 0.053) and in node negative cases (80.1 ± 3.6% vs. 96.2 ± 3.8%, P = 0.052), but it did not reach significance. 5y-OS was similar between IMPC and TNBC (81.9 ± 4.7% vs. 79.8 ± 3.1%, P = 0.475). Conclusions: IMPC is featured with high rate of lymph node involvement which is strongly associated with high rate of LRR. TNBC is featured with high rate of early distant metastasis without increase of nodal metastases. The survival is still relatively poor even in node negative cases. Highlights: We compared clinicopathologic characteristics and prognosis of IMPC and TNBC-IDC. pN was the independent prognostic factor of LRRFS and MFS for IMPC. pT and LVI were both independent prognostic factors of MFS and OS for TNBC. IMPC exhibited more aggressive features with lower LRRFS rate. TNBC had a tendency of lower MFS rate and poor prognosis in node negative cases.